3-Dimensional Craniofacial Imaging: A Template for Systematic Radiologic Evaluation for Alveolar Cleft Assessment and Planning. (April 2023) - Preston, Kathryn; Mallya, Sanjay M.
Background: Imaging findings are central to the diagnosis and treatment planning decisions when managing craniofacial differences. However, limited information is published on protocols for systematic cleft imaging assessment and for effective communication of these findings. Solution: A template is presented to help guide radiologic imaging reports to acquire the relevant clinical information needed to manage patients with alveolar cleft.